1992
DOI: 10.1111/j.1432-1033.1992.tb16845.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and excretion of gangliosides by the isolated perfused rat liver

Abstract: De novo synthesis and excretion into perfusate and bile fluid of hepatic gangliosides were studied in isolated perfused rat livers. Addition of N-a~etyl-[6-~H(n)]~-mannosamine to the perfusate resulted in radioactive synthesis of at least eight gangliosides labeled in their sialic acid residues. About 10% of total de novo synthesized gangliosides were excreted into the perfusate, less than 1% into the bile fluid. Labeled gangliosides were tentatively identified by cochromatography with known standards. All of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Although we presently do not have enough evidence to indicate the means by which hydroxylated GM3 molecular species are enriched in the individuals of VFA with metabolic disease, the observation that hydroxylated GM3 molecular species are far more abundant than hydroxylated ceramide molecular species seems to point to the mechanism of direct hydroxylation. It is interesting to note that a linear correlation has been reported between GM3 molecular species containing hydroxylated acyl chains and aging in the human liver [ 30 ], the site of excretion of gangliosides into mammalian sera [ 25 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we presently do not have enough evidence to indicate the means by which hydroxylated GM3 molecular species are enriched in the individuals of VFA with metabolic disease, the observation that hydroxylated GM3 molecular species are far more abundant than hydroxylated ceramide molecular species seems to point to the mechanism of direct hydroxylation. It is interesting to note that a linear correlation has been reported between GM3 molecular species containing hydroxylated acyl chains and aging in the human liver [ 30 ], the site of excretion of gangliosides into mammalian sera [ 25 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The composition of gangliosides in liver tissues not only shows species-specific patterns, but also varies among different strains of inbred animals (Nilsson and Svennerholm, 1982;Ghidoni et al, 1983;Kasai et al, 1993). Metabolic studies of liver gangliosides have also been conducted using in vivo or organ-perfusion systems (Trinchera et al, 1990a, b;Senn et al, 1992) and in vitro cultures of isolated hepatocytes with radiolabeled precursors (Rump et al, 1986;Mesaric and Decker, 1990;Merrill et al, 1995). While it has been demonstrated that the metabolism of hepatic gangliosides is influenced by hormones (Phillips et al, 1985) or aging (Phillips et al, 1985;Nakamura et al, 1988), information on the regulatory factors for the expression of gangliosides in the liver remains limited.…”
Section: Introductionmentioning
confidence: 98%
“…They have sphingosine‐fatty acid amide linkage and sialic acid and thus, gangliosides are sialic acid or N ‐acetylneuraminic acid (NeuAc)‐containing GSLs [Tettamanti, ; Chung et al, ; Jin et al, ; Kim et al, ; Ha et al, ]. Plasma free gangliosides or lipoprotein‐assembled glycolipids are mainly synthesized from liver and secreted to serum [Senn et al, ]. Various gangliosides have been structurally isolated from plasma in the forms of free or lipoprotein‐associated assembly [Senn et al, ; Rebba and Portoukalian, ; Tettamanti, ].…”
mentioning
confidence: 99%